Development of 10-Hydroxycamptothecin-crizotinib conjugate based on the synergistic effect on lung cancer cells. (1st January 2023) - Liu, Zhen; Xu, Ye; Guo, Lvqian; Li, Xinran; Gao, Junling; Xie, Weiran; Zhao, Lianbo; Teng, Yuou; Li, Xuejiao; Yu, Peng
Abstract: The effect of the combination of 10-Hydroxycamptothecin (HCPT) and crizotinib (CRI) on EGFR- and KRAS-mutant lung cancer cells was investigated and the conjugates of the two drugs were synthesised. HCPT combined with CRI synergistically inhibited the cell growth and proliferation of H1975, HCC827, and H460 without aggravating adverse effect on the normal cells. The combination synergistically enhanced the cell apoptosis rate through releasing Cyto-C by activation of Bcl-2 family-mediated mitochondrial signalling, which was associate with inactivating of EGFR related downstream signalling pathways including AKT, ERK, JNK, and p38 MAPK. Based on this synergy, the conjugates of HCPT and CRI (compounds CH-1 and CH-2 ) with different chemical bonds were synthesised. Compound CH-1 exhibited stronger cytotoxicity than HCPT and CRI alone or in combination. The combination of HCPT and CRI might be a promising therapeutic regimen and the conjugate CH-1 was a potential target drug for the treatment of lung cancer. Graphical abstract: UF0001